Health communication campaign of Clean and Healthy Living Behaviour (PHBS) in Covid-19 pandemic era - Wiyane, Wayan Tantre; Mansur, Suraya (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article explains the results of a research about the health communication campaign on Clean And Healthy Living Behaviour (PHBS) or clean and healthy lifestyle behaviour in the era of the Covid-19 pandemic. Utilising a positivistic paradigm, the method employed in this research is a survey explanatory method and quantitative approach. Samples were selected through a purposive sampling technique, among people in Pura Aditya Jaya Rawamangun Jakarta which yielded 119 respondents, with a sampling error of 5%. The technique of data analysis used in this research is simple regression analysis. The result of the research shows that there is a positive influence of counselling and below-the-line media on clean and healthy lifestyle behaviour among people in Aditya Jaya Rawamangun Jakarta temple. However, the variable of Campaign through Counselling is more dominant in influencing the clean and healthy lifestyle behaviour of people in Pura Aditya Jaya Rawamangun Jakarta, compared to the variable of Campaign through below-the-line media. In conclusion, this research proves that the social learning theory is effective in the campaign which results in behavioural changes in society.